Radon isotopes as tracers of climate-sensitive subsurface connectivity in Antarctic permafrost - L. Ruggiero; A. Sciarra; A. Mazzini; F. Florindo; G. Wilson; C. Mazzoli; P. Tuccimei; G. Galli; L. Tositti; A. Zappi; J. Anderson; L. Davidson; et al. (Environmental Research, 2026)

Microalgae, sunlight, and starch: low cell concentration is optimal for outdoor production under nutrient stress - A. Six; P. Chambonnière; P. Alvarez; S. Fon-Sing; C. Lancelon-Pin; J.-L. Putaux; J.-F. Sassi; Y. Li-Beisson; G. Fleury (Bioresource Technology, 2026)

Development of magadiite-whey hybrid composites for the adsorptive removal of xylenol orange dye - S. Benkhatou; F. Ouazani; Y. Chergui; A. Djelad; A. Mokhtar; M. Bouchekara; M. Sassi (International Journal of Environmental Science and Technology, 2025)

Impact of Terrestrial Weather on the Space Weather of the Ionosphere-Thermosphere: Initial Results from a NASA Living with a Star Focused Science Topic - J. Oberheide; D. Aggarwal; B. Bergsson; S. Chakraborty; S. Debchoudhury; M. Dhadly; F. Gasperini; L. Goncharenko; V. L. Harvey; C. Heale; P. Inchin; J. Li; et al. (Surveys in Geophysics, 2025)
The ionosphere-thermosphere (IT) is a convergence point of energy and processes that interconnect Earth’s atmosphere with space. Processes generated by terrestrial weather in the lower atmosphere (i.e., troposphere and stratosphere, altitudes less than ~ 50 km) are recognized by the scientific community as sources of variability in both the structure and composition of the IT. Exposed to persistent wave forcing from terrestrial weather sources and solar and magnetic forcing, the IT is a domain of compelling scientific inquiry that connects thermodynamics, fluid dynamics, electrodynamics and plasma physics. Predicting its space weather is of significant national interest for space situation awareness including the very low earth orbit as the new frontier of space operations. Advancing the understanding of whole atmosphere interconnections between terrestrial and space weather requires coordinated modeling and observational efforts across different spatial and temporal scales. Toward this goal, the National Aeronautics and Space Administration (NASA), through the living with a star (LWS) program, established in 2022 a focused science topic (FST) to study the problem from various angles. In this manuscript we report on the vision, goals and status of the ongoing FST “Impact of Terrestrial Weather on the Ionosphere—Thermosphere”. Initial results show bigger impacts on the IT than hitherto thought and help to more clearly define the state-of-the-art in the context of future NASA missions such as EZIE, DYNAMIC and GDC.

Early Permian post-collisional magmatism induced by extensive removal of the Variscan lithospheric mantle - Andrea Boscaini; Joshua H. F. L. Davies; Morgann G. Perrot; Raffaele Sassi; Claudio Mazzoli; Angelo De Min; Corrado Morelli; Evelyn Kustatscher; Thomas Blanchet-Gavouyère; Andrea Marzoli (Contributions to Mineralogy and Petrology, 2025)

From raw microalgae to bioplastics: Conversion of Chlorella vulgaris starch granules into thermoplastic starch - A. Six; D. Dauvillée; C. Lancelon-Pin; A. Dimitriades-Lemaire; A. Compadre; C. Dubreuil; P. Alvarez; J.-F. Sassi; Y. Li-Beisson; J.-L. Putaux; N. Le Moigne; G. Fleury (Carbohydrate Polymers, 2024)

Red light induces starch accumulation in Chlorella vulgaris without affecting photosynthesis efficiency, unlike abiotic stress - A. Six; A. Dimitriades-Lemaire; C. Lancelon-Pin; J.-L. Putaux; D. Dauvillée; D. Petroutsos; P. Alvarez Diaz; J.-F. Sassi; Y. Li-Beisson; G. Fleury (Algal Research, 2024)

Artificial intelligence for tunnel boring machine penetration rate prediction - A. Flor; F. Sassi; M. La Morgia; F. Cernera; F. Amadini; A. Mei; A. Danzi (Tunnelling and Underground Space Technology, 2023)

Antarctic permafrost degassing in Taylor Valley by extensive soil gas investigation - L. Ruggiero; A. Sciarra; A. Mazzini; F. Florindo; G. Wilson; M.C. Tartarello; C. Mazzoli; J.T.H. Anderson; V. Romano; R. Worthington; S. Bigi; R. Sassi; et al. (Science of The Total Environment, 2023)

Simulations of the flow in the Mahakam river–lake–delta system, Indonesia - Chien Pham Van; Benjamin de Brye; Eric Deleersnijder; A. J. F. Hoitink; Maximiliano Sassi; Benoit Spinewine; Hidayat Hidayat; Sandra Soares-Frazão (Environmental Fluid Mechanics, 2016)

Ecological and biogeographic implications of Siderastrea symbiotic relationship with Symbiodinium sp. C46 in Sal Island (Cape Verde, East Atlantic Ocean) - João G. Monteiro; Cristiane F. Costa; Krystyna Gorlach-Lira; William K. Fitt; Sergio S. Stefanni; Roberto Sassi; Ricardo S. Santos; Todd C. LaJeunesse (Marine Biodiversity, 2013)

Tidal impact on the division of river discharge over distributary channels in the Mahakam Delta - Maximiliano G. Sassi; A. J. F. Hoitink; Benjamin de Brye; Bart Vermeulen; Eric Deleersnijder (Ocean Dynamics, 2011)

Determination of the chemical composition of ulvan, a cell wall polysaccharide from Ulva spp. (Ulvales, Chlorophyta) by FT-IR and chemometrics - A. Robic; D. Bertrand; J.-F. Sassi; Y. Lerat; M. Lahaye (Journal of Applied Phycology, 2009)

Antiviral activity of some Tunisian medicinal plants against Herpes simplex virus type 1 - A. Ben Sassi; F. Harzallah-Skhiri; N. Bourgougnon; M. Aouni (Natural Product Research, 2008)

Level ground and uphill cycling ability in elite female mountain bikers and road cyclists - F. M. Impellizzeri; T. Ebert; A. Sassi; P. Menaspà; E. Rampinini; D. T. Martin (European Journal of Applied Physiology, 2007)

Simulations of anthropogenic change in the strength of the Brewer–Dobson circulation - N. Butchart; A. A. Scaife; M. Bourqui; J. de Grandpré; S. H. E. Hare; J. Kettleborough; U. Langematz; E. Manzini; F. Sassi; K. Shibata; D. Shindell; M. Sigmond (Climate Dynamics, 2006)

Prediction of time to exhaustion from blood lactate response during submaximal exercise in competitive cyclists - A. Sassi; S. M. Marcora; E. Rampinini; P. Mognoni; F. M. Impellizzeri (European Journal of Applied Physiology, 2006)

Annual cycle of symbiotic dinoflagellates from three species of scleractinian corals from coastal reefs of northeastern Brazil - Cristiane F. Costa; Roberto Sassi; Fernanda D. Amaral (Coral Reefs, 2005)